POPLAR AND ASPEN STANDS IN UKRAINE - Vysotska, N. Yu.; Tkach, V. P. (Forestry and Forest Melioration, 2018)
Introduction Poplars of Turanga section in Ukraine are presented in Botanical gardens and arboreta only; poplars of Aigeiros, Populus, Tacamahaca, Leucoides sections are presented in forests and protective plantations. High frequency of introgressive hybridization of the Populus genus in nature, a large number of hybrids resulted from controlled crosses, the ability for vegetative propagation, and a considerable number of synonyms lead to confusion in the nomenclature of poplars. Information on species composition, the dynamics of the areas, stock volume and age structure of poplar and aspen stands will allow making timely and objective decisions in forest management, in particular, on the activities planning. Materials and Methods The dynamics of the areas, stock volume, and age structure of poplar and aspen stands was analyzed using mathematical processing of the data from electronic subcompartment database of Production Association “Ukrderzhlisproekt” by the period from 2000 to 2010. In total, we had analyzed over 30,000 subcompartments where poplar and aspen are the main species of the first tree layer. Results As of 01.01.2011, the total forest area of State Forest Resources Agency of Ukraine on which representatives of the Populus genus grow, reached 65,383.5 ha, including the area of 35,545.8 ha on which P. tremula were growing. The main part of poplar areas is located in the Steppe (46.5 %) and Forest-Steppe (38.8 %). Aspen forest stands grow mostly in Forest-Steppe (46.2 %) and Polissya (44.7 %). The stock volume of poplar stands has reached 6,928.9 thousand m3, aspen – 7,536.4 thousand m3. From 2000 to 2010, the areas of poplar and aspen increased as a whole by 30.8 %. The increase in total stock by 32.5 % evidences the aging of forests. The average age of the poplar stands was increased over the years: from 1980 to 1990 – on 8–10 years, from 1990 to 2011 on 4 years, and as of 01.01.2011 it amounted to 47 years, which is considerably higher than the age of maturity of this breed. The average age of aspen stands as of 01.01.2011 amounted to 42 years. It is established that more than 30 % of poplar stands are growing in conditions unsuitable for this species. The accumulation of large areas of mature and overmature stands of poplar resulted in deterioration of their general condition and weakening the ecological and protective functions. Such stands are characterized by low commercial value, which significantly reduces the already limited demand for wood of poplar, and, consequently, reduces the economic effect of the logging in such stands. Conclusions Significant reserves of mature and overmature poplar (over 3 million m3) and aspen (over 2.1 million m3) forest stands and the uneven distribution of their areas by age indicate the urgent need of increasing the number of forestry management activities in such forests.